Hydrogen Energy as Future of Sustainable Mobility - Chakraborty, Suprava; Dash, Santanu Kumar; Elavarasan, Rajvikram Madurai; Kaur, Arshdeep; Elangovan, Devaraj; Meraj, Sheikh Tanzim; Kasinathan, Padmanathan; Said, Zafar (Frontiers in Energy Research, 2022)
Conventional fuels for vehicular applications generate hazardous pollutants which have an adverse effect on the environment. Therefore, there is a high demand to shift towards environment-friendly vehicles for the present mobility sector. This paper highlights sustainable mobility and specifically sustainable transportation as a solution to reduce GHG emissions. Thus, hydrogen fuel-based vehicular technologies have started blooming and have gained significance following the zero-emission policy, focusing on various types of sustainable motilities and their limitations. Serving an incredible deliverance of energy by hydrogen fuel combustion engines, hydrogen can revolution various transportation sectors. In this study, the aspects of hydrogen as a fuel for sustainable mobility sectors have been investigated. In order to reduce the GHG (Green House Gas) emission from fossil fuel vehicles, researchers have paid their focus for research and development on hydrogen fuel vehicles and proton exchange fuel cells. Also, its development and progress in all mobility sectors in various countries have been scrutinized to measure the feasibility of sustainable mobility as a future. This, paper is an inclusive review of hydrogen-based mobility in various sectors of transportation, in particular fuel cell cars, that provides information on various technologies adapted with time to add more towards perfection. When compared to electric vehicles with a 200-mile range, fuel cell cars have a lower driving cost in all of the 2035 and 2050 scenarios. To stimulate the use of hydrogen as a passenger automobile fuel, the cost of a hydrogen fuel cell vehicle (FCV) must be brought down to at least the same level as an electric vehicle. Compared to gasoline cars, fuel cell vehicles use 43% less energy and generate 40% less CO2.